Thermal and corrosion behavior of Ti3C2/Copper composites. (December 2020) - Song, Guichen; Deng, Qihuang; Wang, Bo; Liu, Zhiduo; Ye, Chen; Wei, Xianzhe; Dai, Dan; Pan, Zhongbin; Li, Wei; Song, Shulin; Fu, Li; Lin, Cheng-Te; et al.
Abstract: In virtue of its excellent performance and abundant surface terminations, MXenes, a newly emerged 2D materials, greatly exhibit promising applications in many fields of energy storage and electromagnetic shielding. Ti3 C2, a member of MXenes, is widely investigated in recent years. However, lack for attention in thermal property and corrosion behavior. Here, Copper matrix composites were prepared by Spark Plasma Sintering, in which TiC and few-layer Ti3 C2 nanosheets as filler. The results exhibit corrosion resistance of the Ti3 C2 /Cu composites were improved compared to TiC/Cu composites, benefiting from outstanding electrical conductivity and easily oxidized property of Ti3 C2 . However, the thermal conductivity of Ti3 C2 /Cu composite with the content of 2 wt% Ti3 C2 improves about 15% compared to TiC/Cu composites with same content, resulting from the low inherent thermal conductivity of filler and lattice mismatch between copper and filler. Moreover, the electrical resistance of Ti3 C2 /Cu composites increases about 100% with the content of 2 wt% Ti3 C2 at interfacial contact resistance measurement compared with pure Cu. Meanwhile, the anti-corrosion performance of the Ti3 C2 /Cu composites was improved over pure Cu. This work will broaden appliance field of Ti3 C2 and lay the foundation for the future research. Highlights: The MXene/copper (Ti3 C2 /Cu) composites were prepared by Spark Plasma Sintering. The Ti3 C2 /Cu composite exhibits excellent heat dissipation performance than that of the TiC/Cu composite. The corrosion resistance of the Ti3 C2 /Cu composites were improved compared to pure copper and TiC/Cu composites.